Fibre type transition and training - Schiaffino, S. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The diversity of skeletal muscle fibers has been recognized since long time and it is now traditional to distinguish four major fiber types in mammalian muscles, type 1 or slow and fast 2A, 2X and 2B fibers, based on myosin heavy chain (MyHC) isoform composition. The difference between muscle fibers is not restricted to myosin and myofibrillar proteins, but involves metabolic enzymes (predominance of glycolytic or mitochondrial activities), and any subcellular system, including transmembrane ionic fluxes and intracellular calcium signaling (Schiaffino & Reggiani, 2011). Fiber type profiles vary according to species, most human muscles containing only type 1, 2A and 2X fibers, which differ from the corresponding mouse fibers, thus making dangerous any extrapolation of results from transgenic or knockout studies (Schiaffino, 2010). Muscle fibers differ in speed of shortening and maximal power output, which is ten times greater in human type 2X compared to type 1 fibers, and in the resistance to fatigue, which is much greater in type 1/slow fibers. Although the presence of intermediate fiber types may suggest that muscles consist of a continuous spectrum of fibers rather than distinct fiber types, the existence of clusters of molecular, structural and functional parameters indicate that fiber types do exist. Preferential combinations of specific molecular and functional properties presumably reflect the need to obtain consistent values of specific functions, for example, matching energy production with energy consumption. Gene expression profiles must therefore be compatible with the constraints imposed by electrical, mechanical and metabolic influences. The muscle fiber type composition can change in response to variations in activity levels, however the degree of transformation is limited by intrinsic constraints within specific "adaptive ranges" of possible transitions. This may reflect a relative inflexibility of motor unit properties, whci control the muscle phenotype. On the other hand, the finding that regenerating fast and slow muscles respond differently to the same electrical stimulation pattern suggests that intrinsic differences between muscle cell precursors in fast and slow muscles may contribute to restrict muscle plasticity (Khalovde et al, 2005). Human skeletal muscle can also undergo significant fiber type changes in response to training, for example MyHC-2X isoform is downregulated with increased activity with corresponding up-regulation of MyHC-2A, however fast-to-slow fiber type transformations have not been unambiguously demonstrated in athletes (Harridge, 2007). The signaling pathways which control the muscle fiber phenotype are presently the object of intensive research that will benefit not only sport science but also clinical medicine (Schiaffino et al, 2007; Gundersen, 2011).